Sounding the Call for a Global Library of Underwater Biological Sounds - Parsons, Miles J. G.; Lin, Tzu-Hao; Mooney, T. Aran; Erbe, Christine; Juanes, Francis; Lammers, Marc; Li, Songhai; Linke, Simon; Looby, Audrey; Nedelec, Sophie L.; Van Opzeeland, Ilse; Radford, Craig; et al. (Frontiers in Ecology and Evolution, 2022)
Aquatic environments encompass the world's most extensive habitats, rich with sounds produced by a diversity of animals. Passive acoustic monitoring is an increasingly accessible remote sensing technology that uses hydrophones to listen to the underwater world and represents an unprecedented, non-invasive method to monitor underwater environments. This information can assist in the delineation of biologically important areas via detection of sound-producing species or characterization of ecosystem type and condition, inferred from the acoustic properties of the local soundscape. At a time when worldwide biodiversity is in significant decline and underwater soundscapes are being altered as a result of anthropogenic impacts, there is a need to document, quantify, and understand biotic sound sources–potentially before they disappear. A significant step towards these goals is the development of a web-based, open-access platform that provides: 1) a reference library of known and unknown biological sound sources (by integrating and expanding existing libraries around the world); 2) a data repository portal for annotated and unannotated audio recordings of single sources and of soundscapes; 3) a training platform for artificial intelligence algorithms for signal detection and classification; and 4) a citizen-science-based application for public users. Although individually, these resources are often met on regional and taxa-specific scales, many are not sustained, and collectively, an enduring global database with an integrated platform has not been realized. We discuss the benefits such a program can provide, previous calls for global data-sharing and reference libraries, and the challenges that need to be overcome to bring together bio- and ecoacousticians, bioinformaticians, propagation experts, web engineers, and signal processing specialists (e.g., artificial intelligence) with the necessary support and funding to build a sustainable and scalable platform that could address the needs of all contributors and stakeholders into the future.